An Anthropolinguistic Analysis of Language Use in Anti-Female Genital Mutilation Campaign on @puan_amalhayati Instagram Account - A'yunin, Qurrota; Sajarwa, Sajarwa; Firmonasari, Aprillia (Humanus, 2025)
The Practice of Pemotongan dan/atau Pelukaan Genitalia Perempuan (P2GP) or Female Genital Mutilation/Cutting (FGM/C) remains a serious problem in Indonesia because it is rooted in traditions, religious views, and cultural constructs that have been passed down through generations. The urgency of addressing this topic lies in the medical and social impacts that harm women, as well as the debate over terminology that influences public perception of the practice. This research data was obtained from the Instagram account @puan_amalhayati, which consistently campaigns against FGM/C using alternative terms to replace the term "sunat perempuan." The research focused on analyzing the content of posts, choice of terms, narratives, and netizen responses in the comments section. The method employed was content analysis, utilizing a descriptive-qualitative approach. As an analytical tool, this research refers to anthropolinguistic theory by emphasizing three main indicators: context, language ideology, and indexicality. This theory allows for the disclosure of how language becomes a means of communication as well as an instrument for shaping meaning, identity, and power relations. The research findings indicate that the use of the term P2GP is a linguistic strategy that serves to reposition the meaning of this practice from the realm of religious tradition to the realm of violations against human rights. The narrative constructed by Puan Amal Hayati emphasizes medical, gender, and progressive religious aspects to challenge the legitimacy of tradition. Meanwhile, netizen responses demonstrate an ideological contestation between references to the Kitab Kuning and arguments based on medical and human rights grounds.